Analisis Kontribusi Sistem Pertanian Dusung terhadap Keberlanjutan Penghidupan Masyarakat Suku Alune di Kecamatan Inamosol, Kabupaten Seram Bagian Barat - Media Ruspanah; Johan Matinahoru; Rhony E. Ririhena (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2026)
The dusung agricultural system is a form of traditional agroforestry that develops in Maluku and plays an important role in supporting the sustainability of indigenous peoples' livelihoods. This study aims to analyze the characteristics of the dusung agricultural system and its contribution to the sustainability of the livelihood of the Alune Tribe in Inamosol District, West Seram Regency. The research was carried out in July-August 2025 using a mixed methods approach with a case study design. Sampling was carried out purposively on farmers who own dusung and key informants of indigenous peoples. Data were collected through observation, interviews, documentation, and literature studies, then analyzed using quantitative and qualitative descriptive analysis and farming income analysis. The results of the study show that the dusung system has multistrata and multicommodity characteristics that integrate food crops, horticulture, plantations, fruits, and forestry crops in one land unit. This system contributes to household income through diversifying sources of income and strengthening community food security. From the ecological aspect, dusung plays a role in soil and water conservation, maintaining biodiversity, and increasing environmental stability in hilly areas. From the socio-cultural aspect, the dusung system maintains local values such as masohi, sasi, and kewang as a form of customary institutions in the management of natural resources. However, the sustainability of the dusung system still faces obstacles in the form of limited market access, low technology adoption, and reduced interest of the younger generation in the traditional agricultural sector.